2014
DOI: 10.1016/j.humov.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different swimming race constraints on turning movements

Abstract: a b s t r a c tThe aim of this study was to investigate the effects of different swimming race constraints on the evolution of turn parameters. One hundred and fifty-eight national and regional level 200-m (meters) male swimming performances were video-analyzed using the individualized-distance model in the Open Comunidad de Madrid tournament. Turn (p < .001, ES = 0.36) and underwater distances (p < .001, ES = 0.38) as well as turn velocity (p < .001, ES = 0.69) significantly dropped throughout the race, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
1
14
0
2
Order By: Relevance
“…This undoubtedly represented a positive impact on the lap velocities (Vennell, Pease, & Wilson, 2006) which could explain why elite swimmers maintained race pace at the end of the 200 m races. Compared to swimmers of a lower level of expertise, finalists and semi-finalists at the 2013 World Swimming Championships travelled faster underwater velocities than the national and regional level swimmers (typically below 2 m · s -1 ) and showed lower velocity losses underwater (typically 1% from the first to the last turn) (Veiga, Cala, et al 2014;Veiga, Mallo, et al, 2014). Previous research had demonstrated a greater ability of elite swimmers to cope with fatigue on the swimming components of the 200 m races (Figueiredo et al, 2011) but no data on the progression of their underwater swimming had been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This undoubtedly represented a positive impact on the lap velocities (Vennell, Pease, & Wilson, 2006) which could explain why elite swimmers maintained race pace at the end of the 200 m races. Compared to swimmers of a lower level of expertise, finalists and semi-finalists at the 2013 World Swimming Championships travelled faster underwater velocities than the national and regional level swimmers (typically below 2 m · s -1 ) and showed lower velocity losses underwater (typically 1% from the first to the last turn) (Veiga, Cala, et al 2014;Veiga, Mallo, et al, 2014). Previous research had demonstrated a greater ability of elite swimmers to cope with fatigue on the swimming components of the 200 m races (Figueiredo et al, 2011) but no data on the progression of their underwater swimming had been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some research studies further analysed these strategies of competitive swimmers by determining the contribution of the underwater distances to each 50 m race lap. Veiga et al reported that national level swimmers travelled underwater a maximum of 10 m after the turning wall (Veiga, Cala, Frutos, & Navarro, 2014) and that the underwater distance was usually decreased 0.6 m throughout the three turning segments of 200 m races (Veiga, Mallo, Navandar, & Navarro, 2014). The greater capacity of national level swimmers was also described to maintain the underwater parameters at the end of race in comparison to lower level swimmers.…”
Section: Introductionmentioning
confidence: 99%
“…Our results of the linear and cubic models confirm recent studies showing that glide speed after the dive and turn is higher than the mean swimming speed for most high-level swimmers. 50,51 However, Puel et al 52 suggested that there is not only one profile of turn, but instead the swimmers must find the best compromise to applied the highest force in the shortest turn time. This In the linear, quadratic and cubic patterns modeling the intra-lap speed variations, the speed always decreased before the turn, confirming that the turn is one of the major taskconstraint, as already observed by Veiga et al 51,12,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Además, esta distancia fue superior a la encontrada tras el viraje por Veiga et al (2014b) en los nadadores de nivel nacional (4,81±0,71 m), estando más próxima a la de los estilos mariposa y espalda de estos autores. Sin embargo, esta distancia fue inferior a la hallada por Burkett, Mellifont y Mason (2010) tras la salida de crol entre nadadores olímpicos y paralímpicos (8,87±0,66 m).…”
Section: Tiempo Subacuático En Función Del Género De Nadounclassified
“…Un mayor tiempo (4,32±0,12 y 0,88±0,04 s) y distancia (6,47±0,17 y 1,17±0,05 m) durante las fases del movimiento ondulatorio subacuático y la transición al nado, pudieron condicionar la velocidad del nado subacuático. En cambio, este dato difiere de otras investigaciones (Veiga et al, 2014b;Veiga y Roig, 2016b), ya que mariposa fue el estilo más lento (1,63±0,15 m/s y 1,83±0,05 -1,71±0,07 m/s), siendo mayor la velocidad de espalda (2,21±0,21 m/s y 2,15±0,10 -2,09±0,10 m/s). Además, la velocidad del estilo de mariposa mostrada por estos autores fue inferior a la del estudio, a pesar de que los nadadores se impulsaron desde la pared.…”
Section: Velocidad Subacuática En Función Del Estilo De Nadounclassified